2012
DOI: 10.1080/00207721.2011.564320
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and control of Hammerstein system using B-spline approximation and the inverse of De Boor algorithm

Abstract: In this article a simple and effective controller design is introduced for the Hammerstein systems that are identified based on observational input/output data. The nonlinear static function in the Hammerstein system is modelled using a B-spline neural network. The controller is composed by computing the inverse of the B-spline approximated nonlinear static function, and a linear pole assignment controller. The contribution of this article is the inverse of De Boor algorithm that computes the inverse efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
0
17
0
2
Order By: Relevance
“…With the number of knots and their location determined, conventional nonlinear optimization algorithms are applicable for determining the weights and the shaping parameters. Note that if l j ¼ 1=d (8j) the NURB network based Hammerstein systems becomes a nonrational B-spline based Hammerstein systems [26], for which the system identification can be carried out iteratively in practice. The number and locations of knots are predetermined to produce a model as small as possible that can still provide good modelling capability.…”
Section: The Hammerstein Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…With the number of knots and their location determined, conventional nonlinear optimization algorithms are applicable for determining the weights and the shaping parameters. Note that if l j ¼ 1=d (8j) the NURB network based Hammerstein systems becomes a nonrational B-spline based Hammerstein systems [26], for which the system identification can be carried out iteratively in practice. The number and locations of knots are predetermined to produce a model as small as possible that can still provide good modelling capability.…”
Section: The Hammerstein Systemmentioning
confidence: 99%
“…In this study, the controller consists of computing the inverse of the nonlinear static function approximated by NURB, followed by a linear pole assignment controller. The linearization of the closed loop system is achieved by inserting the inverse of the identified static nonlinearity via the inverse of De Boor algorithm [26] which was introduced for the control of B-spline based Hammerstein systems. It is shown that the inverse of De Boor algorithm [26] is also applicable to NURB based Hammerstein systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the assumption that the inverse of De Boor algorithm [14]) can cancel the nonlinearity in the system which is modeled by the identified NURB model, the required controller polynomials are estimated. The reference signals r(t) are generated as a series of sinusoidal wave with its magnitude and frequency changing every 200 time steps.…”
Section: An Illustrative Examplementioning
confidence: 99%
“…In this study, the controller consists of computing the inverse of the nonlinear static function approximated by NURB, followed by a linear pole assignment controller. The linearization of the closed loop system is achieved by inserting the inverse of the identified static nonlinearity via the inverse of De Boor algorithm [14] which was introduced for the control of B-spline based Hammerstein systems.…”
Section: Introductionmentioning
confidence: 99%